2007
DOI: 10.1051/kmae:2007007
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Annual Gonadal Development and Gonadal Ultrastructure in Spiny-Cheek Crayfish (Orconectes Limosus)

Abstract: The aim of this study was to follow the gonadal development in freshwater crayfish Orconectes limosus (Rafinesque) by histological examination of ovaries and testes as well as monthly investigation of the gonadosomatic index over a period of one year. Male gonadosomatic index (I G ) ranged between 0.11 to 0.79% with a minimum in July (0.11%) and maximum in September (0.79%) while in females it ranged between 0.25 to 6.15% with a minimum in July (0.25%) and maximum in April (6.15%). Between April and May, the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…On the contrary, in our study the sex ratio of O. limosus populations was unbalanced towards males, as reported in other studies on this species Pilotto et al, 2008). The male-biased sex ratio notwithstanding, O. limosus abundance appeared to increase quickly in all the monitored populations, probably due to the fast growth rate, high fertility, and early sexual maturity reported for this species (Kozák et al, 2007;Souty-Grosset et al, 2006).…”
Section: Morphometrysupporting
confidence: 66%
“…On the contrary, in our study the sex ratio of O. limosus populations was unbalanced towards males, as reported in other studies on this species Pilotto et al, 2008). The male-biased sex ratio notwithstanding, O. limosus abundance appeared to increase quickly in all the monitored populations, probably due to the fast growth rate, high fertility, and early sexual maturity reported for this species (Kozák et al, 2007;Souty-Grosset et al, 2006).…”
Section: Morphometrysupporting
confidence: 66%
“…The droplets that are seen in H. gammarus for the first time in the vitellogenic oocytes, do not stain with Bromophenol blue and Alcian blue and produce a PAS negative reaction. This is indicative of lipid-like characteristics, as seen in A. leptodactylus [23,[31][32][33]. Kulkarni et al [34] do not mention lipid droplets in their definition of vitellogenesis in P. clarkii.…”
Section: Ovarymentioning
confidence: 99%
“…The mature oocytes store yolk intensely and are ready for spawning in H. gammarus, as in other taxa. At this stage, the mature oocytes of H. gammarus have a smaller size compared with those of Virilastacus araucanius [35], Orconectes limosus [33], C. quadricarinatus [25,30,36], P. clarkii [21] and A. leptodactylus [23]. The yolk granules are abundant in the periphery of the mature oocytes, closest to the cell membrane.…”
Section: Ovarymentioning
confidence: 99%
“…Also, histology reveals both spermatocytes and oocytes. Among the cambarids, Kozák et al (2007) reported that during the mating season of O. limosus the male spermatophores were predominantly filled with spermatozoa and sperm was also noted in the vas deferens. However, two out of 15 males sampled during the winter were found to be intersex, in which atretic oogonia and oocytes were present at the periphery of testicular tissue and occupied less than 15% of testicular tissue.…”
Section: Intersexualitymentioning
confidence: 99%